Residual characteristics and potential integrated risk assessment of synthetic pyrethroids in leafy vegetables from Zhejiang in China – Based on a 3-year investigation. (15th December 2021) - Zhang, Quan; Ying, Zeteng; Tang, Tao; Guo, Bin; Gu, Sijia; Fu, Lili; Dai, Wei; Lin, Shu
Highlights: 19% leafy vegetable samples contained synthetic pyrethroids. 81 samples were detected with more than 2 SPs. The detection rate of the individual SP tended to show a downward trend. Dietary exposures of synthetic pyrethroids in leafy vegetables were acceptable. Abstract: Leafy vegetables have high nutritional value and are very popular in China. However, the long-term variation in residues and integrated risks of synthetic pyrethroids (SPs) in these vegetables have not been well examined. In this study, a total of 1005 samples were collected from 55 markets during 2017–2019. The cumulative exposure to nine kinds of SPs in Zhejiang, China, through the consumption of nine leafy vegetables was analyzed, and the potential integrated risk was assessed by the relative potency factor. A total of 191 samples were detected with SPs residues. The most frequently detected SPs were λ-cyhalothrin and cypermethrin. The integrated risk assessment results revealed that the dietary risk for these SPs via leafy vegetable exposure is acceptable for children, adults and elderly individuals. The data provided here will be helpful for the government to formulate food policies in China.